Synthesis, Characterization and Antimicrobial Activity of Embelinthiosemicarbazone and its Transition Metal Complexes - REMA DEVI, V.K.; FERNANDEZ, ANNETTE; ALAUDEEN, M. (Asian Journal of Chemistry, 2010)
Embelinthiosemicarbazone (ETSC) bas been synthesized by condensing embelin with thiosemicarbazide. The complexes of ETSC with metal ions Cu(II), Ni(ll), Co(II), Mn(lI), Zn(II), Cd(II), VO(lI), UO2(II), MoO2(II), Fe(Ill) and Cr(III) were synthesized and characterized using various spectral techniques like UV, IR, 1H NMR and magnetic and conductance measutements. Embelin, ETSC and a few metal complexes of ETSC were screened for their antibacterial antifungal and anthelmintic activities.